2013
DOI: 10.1152/ajpgi.00054.2013
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory muscle training improves antireflux barrier in GERD patients

Abstract: Nobre e Souza MÂ, Lima MJ, Martins GB, Nobre RA, Souza MH, de Oliveira RB, dos Santos AA. Inspiratory muscle training improves antireflux barrier in GERD patients. Am J Physiol Gastrointest Liver Physiol 305: G862-G867, 2013. First published October 10, 2013 doi:10.1152/ajpgi.00054.2013.-The crural diaphragm (CD) is an essential component of the esophagogastric junction (EGJ), and inspiratory exercises may modify its function. This study's goal is to verify if inspiratory muscle training (IMT) improves EGJ mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 26 publications
4
23
0
2
Order By: Relevance
“…The emphasis on inspiratory as opposed to expiratory EGJ pressure is also supported by preliminary work with 3D‐HRM, demonstrating that the hiatus and CD dominate over the intrinsic LES in defining EGJ barrier function . Preliminary data utilizing inspiratory muscle training as an effective therapeutic intervention in GERD also support this contention …”
Section: Interpreting the Hrm Studymentioning
confidence: 76%
“…The emphasis on inspiratory as opposed to expiratory EGJ pressure is also supported by preliminary work with 3D‐HRM, demonstrating that the hiatus and CD dominate over the intrinsic LES in defining EGJ barrier function . Preliminary data utilizing inspiratory muscle training as an effective therapeutic intervention in GERD also support this contention …”
Section: Interpreting the Hrm Studymentioning
confidence: 76%
“…We recently showed that esophagitis patients failed to achieve a high EGJ pressure during inspiratory maneuvers by conventional manometry. Furthermore, EGJ pressures and GERD symptoms improved after inspiratory muscle training . Two other groups have showed that respiratory exercises may improve GERD .…”
Section: Discussionmentioning
confidence: 92%
“…Firstly, without airflow resistance, the volunteers carried out six cycles of 5‐second deep inhalation and 5‐second exhalation (sinus arrhythmia maneuver [SAM]). Secondly, with airflow resistance, they did a fast and forced inhalation through a device that incorporated a flow‐independent one‐way spring‐loaded valve that provided an adjustable airflow resistance (Threshold IMT; Philips Respironics, Andover, MA, USA) . Each subject trained the maneuvers during few minutes before the study and accomplished inhalations under increasing, resistance loads of 12‐, 24‐, and 48‐cmH 2 O (threshold maneuver [TH]).…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have demonstrated the beneficial effects of DB on esophageal functions. Thus, DB decreased swings in the gastroesophageal pressure gradient when compared to rib breathing, and reduced reflux in patients with upright gastroesophageal reflux disease while inspiratory muscle training significantly increased EGJ pressure …”
Section: Discussionmentioning
confidence: 95%